Tuck - Lawhead, Stephen R., 1950- (Lawhead, Stephen R., 1950- King Raven trilogy, 2009)
Abbot Hugo plans to bring the invading Norman marchogi to the forest in force, heralding the start of a campaign to wipe out King Raven and his band once and for all. But Friar Tuck, a most unconventional priest, may just have a solution to the band's desperate dilemma.